The Influence of High and Low Negative Pressure Liposuction and Various Harvesting Techniques on the Viability and Function of Harvested Cells-a Systematic Review of Animal and Human Studies - Molitor, Martin; Trávníčková, Martina; Měšťák, Ondřej; Christodoulou, Petros; Sedlář, Antonín; Bačáková, Lucie; Lucchina, Stefano (Aesthetic plastic surgery, 2021)
BACKGROUND: An understanding of fat grafting methodology, techniques and patient-related factors is crucial when considering fat grafting. Multiple factors can influence the success of a fat graft and consequently the outcome of the procedure. The aim of this systematic review is to elucidate the influence of negative pressure and various techniques of fat harvesting on the viability and function of cells, particularly adipocytes and adipose-derived stem cells. METHODS: We conducted a literature search from 1975 to 2020 using the PubMed bibliography, ScienceDirect, SCOPUS and the Google Scholar databases which produced 168,628 articles on the first pass. After applying all the exclusion criteria by two independent reviewers, we were left with 21 articles (level IV of Oxford Centre for Evidence-Based Studies and Grade C of Grade Practice Recommendation from the American Society of Plastic Surgeons) on which this review is based. RESULTS: From 11 studies focused on different negative pressures, no one found using high negative pressure advantageous. Summarising 13 studies focused on various harvesting techniques (excision, syringe, and pump-machine), most often equal results were reported, followed by excision being better than either syringe or liposuction. CONCLUSION: From our systematic review, we can conclude that the low negative pressure seems to yield better results and that the excision seems to be the most sparing method for fat graft harvesting. However, we have to point out that this conclusion is based on a very limited number of statistically challengeable articles and we recommend well-conducted further research. LEVEL OF EVIDENCE III: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .
Keywords: Negative pressure; tuková tkáň; Tissue and Organ Harvesting; Humans; Transplantation, Autologous; lipektomie; Fat grafting; autologní transplantace; výsledek terapie; Liposuction; lidé; zvířata; odběr tkání a orgánů; Lipectomy; Adipocytes; tukové buňky; Treatment Outcome; Adipocyte; Animals; Adipose Tissue; ADSC